2021
DOI: 10.1080/02673037.2021.1941793
|View full text |Cite
|
Sign up to set email alerts
|

Collective self-build for senior friendly communities. Studying the effects on social cohesion, social satisfaction and loneliness

Abstract: Neighbourhood social cohesion is important for the health and well-being of the ageing population. It is therefore crucial to study how we can create neighbourhoods with high levels of neighbourhood social cohesion where senior citizens can age in place. We test the hypotheses that collective self-build is positively related to social cohesion and (directly and indirectly) to social satisfaction and lower levels of loneliness. The study is based on survey data from 326 respondents of 50 years and over living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This study showed that older adults develop their focus from community life, even if they live alone; they could also receive mental health benefits from community interactions, such as religious or volunteer activities. This result is consistent with many prior studies [34,35,55,111,112]. In terms of social support, the results showed that older adults receive care, attention, and respect when they participate ingroup activities, increasing social networks and reducing social isolation [113].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that older adults develop their focus from community life, even if they live alone; they could also receive mental health benefits from community interactions, such as religious or volunteer activities. This result is consistent with many prior studies [34,35,55,111,112]. In terms of social support, the results showed that older adults receive care, attention, and respect when they participate ingroup activities, increasing social networks and reducing social isolation [113].…”
Section: Discussionsupporting
confidence: 92%
“…Group activities are becoming more and more important in the social life of older adults, and people are paying more and more attention to maintaining the connection and cohesion of the living environment of older adults, which is also an important way to prevent loneliness [34]. Therefore, increasing social interaction and social cohesion through community activities, schools for older adults, volunteer service groups, and participation in religious activities can prevent loneliness and promote mental health [35]. In addition, studies have pointed out that if older adults have positive social cohesion, this has a positive impact on mental health and can reduce depression, hopelessness, and loneliness [36].…”
Section: Introductionmentioning
confidence: 99%
“…This aligns senior cohousing more closely with the concept of active aging than with the traditional idea of retirement [ 34 ]. There is a positive relationship between collective self-build and social cohesion [ 35 ] and the cohousing residents’ intention to live together as active, mutually supportive participants in their community of neighbors creates a shared environment that fosters communication, the exchange of skills, and continuous learning [ 36 ].…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%